Glukokortikoide bei nichtendokrinen Erkrankungen, bei Kortisolmangel und bei endogenem Exzess – der Einfluss therapeutischer Strategien auf das kindliche Wachstum - Hauffa, B. P.; Binder, G.; Bonfig, W.; Bettendorf, M.; Dörr, Helmuth-Günther (Monatsschrift Kinderheilkunde, 2019)
Background: Adrenocortical hormones can influence the growth of children and adolescents. Objective: How does chronic glucocorticoid treatment of nonendocrine diseases and endogenous Cushing’s syndrome affect growth? What has to be considered during the treatment of patients with central adrenal cortex insufficiency under growth hormone substitution and patients with congenital adrenal hyperplasia with respect to growth? Material and methods: This article is based on the results of a workshop held by pediatric endocrinologists. Each author conducted a recent literature research on growth under the specific aspects of adrenal cortex physiology and pathology and the respective treatment procedures. Results: The therapeutic use of high doses of synthetic glucocorticoids for nonendocrine disorders (pharmacological treatment) inhibits the growth of children and adolescents. Long-term use should therefore be avoided and glucocorticoid-sparing treatment regimens (biologicals etc.) should be preferred. High endogenous cortisol levels in Cushing’s syndrome cause growth retardation; however, if the secretion of androgens predominates, longitudinal growth can also be increased. In patients with growth hormone deficiency, the possibility of a delayed failure of the hypothalamus-pituitary-adrenal cortex axis has to be considered and a re-evaluation should be scheduled. High doses of hydrocortisone during substitution should be avoided so as not to compromise the effect of the growth hormone therapy (substitution therapy). Patients with congenital adrenal hyperplasia and 21-hydroxylase deficiency show specific growth characteristics in the different phases of life. It is therefore a therapeutic challenge to achieve a normal final body height by individually adapting glucocorticoid treatment. Conclusion: The adequate diagnosis, treatment and monitoring of disorders of adrenal cortex function are important to minimize the negative effects on the growth of children and adolescents.
CRIS-Team Scopus Importer:2019-06-07
Keywords: Adrenal glands; Congenital adrenal hyperplasia; Cushing’s syndrome; Hydrokortisone; Synthetic Glucocorticoids